A Novel Dual-Band Binary Branch Fractal Bionic Antenna for Mobile Terminals - Xiaoying Ran; Zhen Yu; Tangyao Xie; Yao Li; Xiuxia Wang; Peng Huang (International Journal of Antennas and Propagation)
A novel two-iteration binary tree fractal bionic structure antenna is proposed for the third generation (3G), fourth generation (4G), WLAN, and Bluetooth wireless applications in the paper, which is based on the principles of conventional microstrip monopole antenna and resonant coupling technique, combined with the advantages of fractal geometry. A new fractal structure was presented for antenna radiator, similar to the tree in nature. The proposed antenna adapted two iterations on a fractal structure radiator, which covers mobile applications in two broad frequency bands with a bandwidth of 44.2% (1.85–2.9 GHz) for TD-SCDMA, WCDMA, CDMA2000, LTE33-41, and Bluetooth frequency bands, and 11.5% (4.9–5.5 GHz) for WLAN frequency band. The proposed antenna was fabricated on a G10/FR4 substrate with a dielectric constant of 4.4 and a size of 50 × 40 mm2. The good agreement between the measurement results and the simulation results validate that the proposed design approach meet the requirements for various wireless applications.